Impact of acceptor concentration on the resistivity of Ni/Au p‐contacts on semipolar (20–21) GaN:Mg. Issue 1 (12th October 2015) - Rychetsky, M.; Koslow, I. L.; Wernicke, T.; Rass, J.; Hoffmann, V.; Weyers, M.; Kneissl, M.
Abstract : The p‐type doping of GaN with Mg, in particular doping of p ++ cap layers and its influence on the resistivity of Ni/Au contacts on semipolar (20–21) GaN, has been investigated. For this purpose, we have compared GaN:Mg grown on several semipolar and polar orientations with respect to the acceptor concentration N A measured by electrochemical capacitance voltage techniques. For the same Mg precursor flow and Mg/III ratio, we observe very similar acceptor densities N A of up to 1 × 10 19 cm −3 for (0001), (20–21), (20–2–1), and (11–22) GaN:Mg. Furthermore, the impact of the II/III ratio for the p ++ cap layer ( N A > 1 × 10 19 cm −3 ) on I – V characteristics of Ni/Au (20 nm/30 nm) contacts on (20–21) oriented GaN:Mg has been investigated. Ohmic I – V characteristics were observed for Mg/III ratios >1 × 10 −2 . Specific contact resistivities as low as 2.4 × 10 −3 Ω cm 2 could be achieved. Inclusion of this p ++ cap layer resulted in reduced turn on voltages in light emitting diodes with 450 nm emission wavelength.